Influence of violence perpetrated by an intimate partner in the practice of breastfeeding (Research, Society and Development, 2022)
The study aimed to investigate the repercussions of different forms of intimate partner violence on initiation and continuity practices of breastfeeding. An integrative literature review was carried out between 2008 and 2020 in the PubMed database, Virtual health Library (VHL) and Scientific Eletronic Library Online (SciELO). The descriptors used to search for the articles were breastfeeding, violence against women, breastfeeding and violence. To perform the bibliographic search, the Methodology Focused on Clinical Research was adopted and to select and evaluate the articles, the Preferred Reporting Items for Systematic reviews and Meta-Analyses was used as a strategy. To verify the level of evidence in the studies, the instrument recommended by Gershon et al. (1999) was used. Forty articles were found, of which 23 met the inclusion criteria. Of the selected articles, the majority were published between 2018 and 2020. Of these, 11 had a cross-sectional design (48%) and seven were cohort (30%). It was evidenced that the association between breastfeeding and intimate partner violence, harms early initiation, maintenance and exclusivity of breastfeeding.